A Green's function approach to giant-dipole systems. (21st December 2017) - Stielow, Thomas; Scheel, Stefan; Kurz, Markus
Abstract: In this work we perform a Green's function analysis of giant-dipole systems. First, we derive the Green's functions of different magnetically field-dressed systems, in particular of electronically highly excited atomic species in crossed electric and magnetic fields—so-called giant-dipole states. We determine the dynamical polarizability of atomic giant-dipole states as well as the adiabatic potential energy surfaces of giant-dipole molecules in the framework of the Green's function approach. Furthermore, we perform an comparative analysis of the latter to an exact diagonalization scheme and show the general divergence behavior of the widely applied Fermi-pseudopotential approach. Finally, we derive the giant-dipole's regularized Green's function representation.